Prioritizing NAP Implementation for Resilient Futures in the Global South in the Wake of COP28 - Disha, Jannatul Shareat (國際人文社科研究, 2024)
In alignment with the theme of climate change, the United Nations convenes annual Climate Change Conferences (COPs) to deliberate on particular topics or agendas that demand urgent and immediate consideration (United Nations Climate Change, 2023). The most recent conference, COP28, was held in Dubai, an additional defining moment in the worldwide effort to combat climate change. The main outcomes of global action were established on four pillars: accelerating a just, orderly, and equitable energy transition; resolving climate finance issues; prioritizing people,lives, and livelihoods; and underpinning everything with complete inclusivity. Amidst the discourse surrounding mitigation, adaptation, and financing, a pivotal element that garnered considerable interest was the execution of National Adaptation Plans (NAPs). In light of the increasing consequences of climate change, especially in susceptible areas such as the Global South, it has become imperative to prioritize the execution of the NAP in order to foster resilience and ensure sustainable futures (UNFCCC, 2023). This piece illuminates how the implementation of NAPs in the Global South can be prioritized following COP28.